Genetic diversity of methicillin resistant Staphylococcus aureus strains in the Pretoria region in South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.